Geography and Intra-National Home Bias: U.S. Domestic Trade in 1949 and 2007 - Nicholas Crafts; Alexander Klein (University of Kent, School of Economics, 2013)
This paper examines home bias in U.S. domestic trade in 1949 and 2007. We use a unique data set of 1949 carload waybill statistics produced by the Interstate Commerce Commission, and 2007 Commodity Flow Survey data. The results show that home bias was considerably smaller in 1949 than in 2007 and that home bias in 1949 was even negative for several commodities. We argue that the difference between the geographical distribution of the manufacturing activities in 1949 and that of 2007 is an important factor explaining the differences in the magnitudes of home-bias estimates in those years.
Keywords: F14; F18; 330; intra-national home bias; spatial clustering; manufacturing belt; gravity equation; Interregionaler Handel; Home Bias Puzzle; Industrie; Regionales Cluster; Gravitationsmodell; Schätzung; USA